BANYUWANGI REGIONAL GOVERNMENT POLICY IN TOURISM DEVELOPMENT AND IT’S CONTRIBUTION TO REGIONAL ORIGINAL INCOME (PAD) - Zaim Mukaffi; Syahirul Alim; Muhammad Tulus (Institute of Computer Science (IOCS), 2022)
This study aims to determine the objective conditions of tourism and government policies and their contribution to PAD in Banyuwangi Regency. The type of research used is a qualitative type with a descriptive approach. The data used in this study are primary and secondary data. As for the data analysis, using a qualitative analysis descriptive approach. The results of the study show that 1. The tourism sector is a strategic sector developed by the Banyuwangi district government and at the same time becomes the starting point for economic development and development while still prioritizing local wisdom and involving the local community without losing local values . 2. Local government policies are divided into 2 approaches, namely: Ecotourism Concept where the concept of tourism development through 3 concepts namely Community based Tourism (CBT), event tourism and a sustainable and structured marketing strategy. Integrated development is integrating between sectors that can be connected with the business sector, namely improving infrastructure, maintaining local culture, and involving the Tourism Community. 3. The development of tourism in Banyuwangi Regency has an impact on PAD, which is 22 billion (5.6%) in 2017, to 29 billion (6.4%) in 2018. Meanwhile in 2019 the development is very significant, which is 37 billion ( 7.4%).